2021
DOI: 10.1002/pts.2594
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured leak rates and calculation values for sealing packages

Abstract: It is often necessary to calculate a leak rate from the size of leak hole and vice versa for testing of sealing packages such as foods, medicines and dangerous goods. These calculations are actually rather complicated because the characteristics of the gas flow through the leak hole change depending on the pressure, the gas species, the temperature and the diameter d and length l of the leak hole. In this study, the air flow rate through 12 flow channels with the inner diameter of 5–50 μm and the l/d ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this case, however, it was found that the gas flow could become turbulent from the calculation of Reynolds number. Therefore, the gas throughput, Q , was calculated by the modified Knudsen equation as shown in eq , which is applicable to the whole flow regime Q = Q VL Q TB ( Q CF Q normalM / 1.235 ) Q VL 2 Q TB 2 + Q TB 2 ( Q CF Q normalM / 1.235 ) 2 + ( Q CF Q normalM / 1.235 ) 2 Q VL 2 + Q M 1 + M italicRT normald η 1 + 1.235 M italicRT normald η where Q VL , Q TB , Q CF , and Q M are the gas throughputs calculated by assuming lamina flow, turbulent flow, compressible flow, and molecular flow, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, however, it was found that the gas flow could become turbulent from the calculation of Reynolds number. Therefore, the gas throughput, Q , was calculated by the modified Knudsen equation as shown in eq , which is applicable to the whole flow regime Q = Q VL Q TB ( Q CF Q normalM / 1.235 ) Q VL 2 Q TB 2 + Q TB 2 ( Q CF Q normalM / 1.235 ) 2 + ( Q CF Q normalM / 1.235 ) 2 Q VL 2 + Q M 1 + M italicRT normald η 1 + 1.235 M italicRT normald η where Q VL , Q TB , Q CF , and Q M are the gas throughputs calculated by assuming lamina flow, turbulent flow, compressible flow, and molecular flow, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the gas throughput, Q, was calculated by the modified Knudsen equation as shown in eq 2, which is applicable to the whole flow regime. 24…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To illustrate the importance of eliminating large holes or cracks in a membrane, crossover rates were modeled using a modified Knudsen model that accounts for both diffusion and convection of H 2 through cylindrical, gas-filled pinholes of arbitrary diameter (d p ) as depicted in Figure 5a. 23 In Figure 5b, the %CR was modeled as a function of pinhole density and pinhole diameter at a differential pressure of 13.8 bar (14.8 bar partial pressure H 2 at the cathode) for a hypothetical membrane with thickness t m = 100 nm and intrinsic H 2 permeability P Hd 2 = 5 × 10 −10 cm 2 s −1 . At low pinhole densities, the crossover rate approaches the value predicted by Fick's Law, which is below the crossover target.…”
mentioning
confidence: 99%
“…To illustrate the importance of eliminating large holes or cracks in a membrane, crossover rates were modeled using a modified Knudsen model that accounts for both diffusion and convection of H2 through cylindrical, gas-filled pinholes of arbitrary diameter (dp) as depicted in Figure 5a. 23 In Figure 5b, the %CR was modeled as a function of pinhole density and pinhole diameter at a differential https://doi.org/10.26434/chemrxiv-2024-qp2rs ORCID: https://orcid.org/0000-0002-0550-801X Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 pressure of 13.8 bar (14.8 bar partial pressure H2 at the cathode) for a hypothetical membrane with thickness tm = 100 nm and intrinsic H2 permeability PH2 = 5x10 -10 cm 2 s -1 .…”
mentioning
confidence: 99%